A Study of Failure Strength for Fiber-Reinforced Composite Laminates with Consideration of Interface. (30th March 2015) - Ye, Junjie; Qiu, Yuanying; Chen, Xuefeng; He, Yumin; Zhai, Zhi
Abstract : Composite laminates can exhibit the nonlinear properties due to the fiber/matrix interface debonding and matrix plastic deformation. In this paper, by incorporating the interface stress-displacement relations between fibers and matrix, as well as the viscoplastic constitutive model for describing plastic behaviors of matrix materials, a micromechanical model is used to investigate the failure strength of the composites with imperfect interface bonding. Meanwhile, the classic laminate theory, which provides the relation between micro- and macroscale responses for composite laminates, is employed. Theory results show good consistency with the experimental data under unidirectional tensile conditions at both 23°C and 650°C. On this basis, the interface debonding influences on the failure strength of the [0/90] s and [0/±45/90] s composite laminates are studied. The numerical results show that all of the unidirectional (UD) laminates with imperfect interface bonding provide a sharp decrease in failure strength in the σ x x - σ y y plane at 23°C. However, the decreasing is restricted in some specific region. In addition, for [0/90] s and [0/±45/90] s composite laminates, the debonding interface influences on the failure envelope can be ignored when the working temperature is increased to 650°C.